KONFLIK PENAMBANGAN EMAS DI KECAMATAN LIMUN KABUPATEN SAROLANGUN - Ulul, Azmi (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2018)
AbstractIn 1970-1999 the development of gold mining in Indonesia was influenced by the centralistic New Order government's economic policies including the gold mining sector. In 1970 the community in Kecamatan Limun still did the gold mining with the traditional model. In the year 2000 mining model undergoing change and development, people doing gold mining using machine. The impact of mining activities on environmental, social, economic and political damage. The government as the policy owner issues a policy, which ultimately leads to conflict. This conflict occurred because of a clash between government policies and the interests of gold miners.Keyword: Conflict, Gold Mining, Limun District